Accumulation of Securin on Spindle During Female Meiosis I - Pauerova, Tereza; Radonova, Lenka; Horakova, Adela; Knott, Jason G.; Anger, Martin (Frontiers in Cell and Developmental Biology, 2021)
Chromosome segregation during female meiosis is frequently incorrect with severe consequences including termination of further development or severe disorders, such as Down syndrome. The accurate chromosome segregation requires tight control of a protease called separase, which facilitates separation of sister chromatids by cohesin cleavage. There are several control mechanisms in place, including binding of specific protein inhibitor securin, phosphorylation by Cyclin Dependent Kinase 1 (CDK1) and complex with SGO2 and MAD2 proteins. All these mechanisms restrict the activation of separase for the time when all chromosomes are properly attached to the spindle. In our study we focused on securin and compared the expression profile of endogenous protein with exogenous securin, which is widely used to study chromosome segregation. We also compared the dynamics of securin proteolysis in meiosis I and meiosis II. Our study revealed that the expression of both endogenous and exogenous securin in oocytes is compartmentalized and that this protein accumulates on the spindle during meiosis I. We believe that this might have a direct impact on the regulation of separase activity in the vicinity of the chromosomes.